Implementation of innovation management strategies for company competitiveness in the e-commerce industry - Boyke Setiawan Soeratin (SEAN Institute, 2024)
Technological advances thanks to the internet have opened new business opportunities, the growth of e-commerce is one of them. E-commerce is one of the advanced technologies that best drives the progress of Indonesia's digital business, the growth of the e-commerce industry is growing very rapidly, of course, it brings its own challenges for business people to be able to compete and survive in this industry, companies need to have the right strategy, one of which is an innovation management strategy. The purpose of this study is to analyze the application of innovation management strategies for company competitiveness in the e-commerce industry. This research uses qualitative research methods. The data collection technique in this research uses the literature study method. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that a good innovation management strategy can help organizations to remain competitive in a growing market, because it can expand market share with new consumers, increase customer satisfaction, and increase company productivity and efficiency. Companies that do not carry out innovation strategies will be at a disadvantage and the company will be more difficult to compete and survive in an era of increasingly fierce competition. The implementation of strategies that can be carried out by companies such as product and service innovation strategies, process innovation strategies, marketing innovation strategies, organizational innovation strategies and business model innovation strategies. Companies that innovate regularly will be able to increase their competitive advantage with their competitors, besides that innovation can also help companies to achieve their business goals. For this reason, it can be concluded that the application of innovation management strategies can increase the competitiveness of companies in the e-commerce industry.